Protestant Ethic, Status Seeking, and Economic Growth - Michael Rauscher (Universität Rostock, Institut für Volkswirtschaftslehre, 1997)
Commodities do not only serve the purpose of satisfying direct needs in the production and con-sumption process. Some of them can also be used to display social status and to affect the position of an individual in society. This paper addresses the question under which circum-stances status-seeking behaviour may lead to permanent economic growth in a simple model. The protestant ethic is interpreted as a special case of status-seeking behaviour. It is shown that societies composed of status-seeking individuals may grow faster than less status-oriented societies.
Keywords: D91; D92; P16; 330; Protestant ethic; social status; economic growth; Sozialer Status; Wirtschaftssoziologie; Neue Wachstumstheorie; Protestantismus; Theorie; Religion